Short Communication. Application of Meta-Analysis if Forestry Related Topics. - Kitikidou, K.; Milios, E.; Stampoulidis, A.; Papageorgiou, A. (Forest Systems, 2013)
Aim of study: Provision of the necessary knowledge to foresters in order carry out objective literature research, through meta-analysis. Area of study:Mediterranean Material and Methods: We describe in detail the methodology of meta-analysis. Then, we apply a meta-analysis in a set of independent studies of density of Aleppo pine (Pinus halepensis Mill.), a common forest species of theMediterranean. Research highlights: Making high quality meta-analyses, can help foresters in making the most of individual forest studies by synthesize them. In this work: We provide details on approaches for undertaking a meta-analysis. We use a silvicultural example to demonstrate our idea. We show how the method of meta-analysis could be applied to forestry also (besides the classical medical study reviews). We have as ultimate goal the use of this article as a reference from other researchers as regards the application of meta-analysis to their area of expertise. Keywords: Literature research; Systematic review.